Robotic system design and development for automated dismantling of PCB waste. Issue 5 (26th February 2021) - Doroftei, Ioan; Chirita, Daniel; Stamate, Ciprian; Cazan, Stelian; Pascal, Carlos; Burlacu, Adrian
Abstract : Purpose: The mass electronics sector is one of the most critical sources of waste, in terms of volume and content with dangerous effects on the environment. The purpose of this study is to provide an automated and accurate dismantling system that can improve the outcome of recycling. Design/methodology/approach: Following a short introduction, the paper details the implementation layout and highlights the advantages of using a custom architecture for the automated dismantling of printed circuit board waste. Findings: Currently, the amount of electronic waste is impressive while manual dismantling is a very common and non-efficient approach. Designing an automatic procedure that can be replicated, is one of the tasks for efficient electronic waste recovery. This paper proposes an automated dismantling system for the advanced recovery of particular waste materials from computer and telecommunications equipment. The automated dismantling architecture is built using a robotic system, a custom device and an eye-to-hand configuration for a stereo vision system. Originality/value: The proposed approach is innovative because of its custom device design. The custom device is built using a programmable screwdriver combined with an innovative rotary dismantling tool. The dismantling torque can be tuned empirically.